Efficiency of water use in different sequences of crops and fallows in Argentina - Golik, Silvina (2022)
Introduction. Water is the most limiting factor in the production of extensive rainfed crops in the Pampas region of Argentina and in many parts of the world. Objective. To determine the water use efficiency, both in grain yield and in total biomass produced, for different crop sequences under different fallow managements. Materials and methods. The trial was carried out in the Experimental Station of the Facultad de Ciencias Agrarias y Forestales, J. Hirschhorn (34 ° 52´ LS, 57 ° 58´ LO), La Plata, Buenos Aires, Argentina, where since 2011 four crop sequences have been working and from 2015, in the period between summer crops, different treatments were implemented that included the use of cover crops with and without fertilization in the successor crop and the application of compost.  During the period 2015 - 2018, total biomass produced, yield, and water use efficiency were determined. Results. The sequence oats (Avena sativa L.) / soybean (Glicine max L.) 2nd - corn (Zea mays L.) - sunflower (Helianthus annuus L.) - wheat (Triticum aestivum L.) was the most efficient in the use of water. In the last place, the sequence wheat / soybean 2nd-soybean-soybean-wheat was found, with the highest frequency of the soybean crop. The different types of fallows affected the water use efficiency, with less efficient values under the control treatment. Conclusion. The crop sequences analyzed showed differences in water use. The fallows with cover crops and compost were more efficient in water use by 10,85 % on average of grain, and in 3,64 % on average of biomass.